1998
DOI: 10.1161/01.str.29.10.2189
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and TIMPs Are Associated With Blood-Brain Barrier Opening After Reperfusion in Rat Brain

Abstract: Background and Purpose-Reperfusion disrupts cerebral capillaries, causing cerebral edema and hemorrhage. Middle cerebral artery occlusion (MCAO) induces the matrix-degrading metalloproteinases, but their role in capillary injury after reperfusion is unknown. Matrix metalloproteinases (MMPs) and tissue inhibitors to metalloproteinases (TIMPs) modulate capillary permeability. Therefore, we measured blood-brain barrier (BBB) permeability, brain water and electrolytes, MMPs, and TIMPs at multiple times after reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
578
1
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 770 publications
(619 citation statements)
references
References 41 publications
35
578
1
5
Order By: Relevance
“…40,83 The rise in MMP-2 correlates with early opening of the BBB and degradation of the TJPs claudin-5 and occludin in rodent MCAO models. 78,80,84,85 In addition, direct injection of MMP-2 into rodent brain disrupts the BBB and results in hemorrhage, further supporting a role of MMP-2 in early BBB disruption and HT in stroke. 84 Though MMP-2 is associated with early BBB disruption after stroke, its role in HT and effect on stroke outcome remains less clear.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 89%
See 2 more Smart Citations
“…40,83 The rise in MMP-2 correlates with early opening of the BBB and degradation of the TJPs claudin-5 and occludin in rodent MCAO models. 78,80,84,85 In addition, direct injection of MMP-2 into rodent brain disrupts the BBB and results in hemorrhage, further supporting a role of MMP-2 in early BBB disruption and HT in stroke. 84 Though MMP-2 is associated with early BBB disruption after stroke, its role in HT and effect on stroke outcome remains less clear.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 89%
“…87 Though the MMP inhibitor (BB-1101) blocked MMP-2 increase in brain, a reduction in cerebral edema and BBB permeability was present only at 24 hours and not at 48 hours. 80 In contrast, a recent study of mice within 1 to 1.5 hours of MCAO found that MMP-2-deficient mice had a reduced rate of HT, smaller hemorrhage volume, and improved neurologic function compared with wild type. 79 The reasons for these differing results require further study to better understand the role of MMP-2 in acute stroke and early HT.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 90%
See 1 more Smart Citation
“…However, open factors such as biphasic opening of postischemic BBB and a relatively weak link between early permeability increase and eventual hemorrhagic transformation warrant investigations for elucidating technical advantage in WEI and involvement of other directly causative factors. 35,36 While further verification with pathologic indices is required for confirming such prognostic potential, the proposed WEI method provides simultaneous assessment of water permeability and CBV, which are closely related to the endogenous sources accountable for vasogenic edema and hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MMP-9 correlates with the time of maximal damage, while the later increase in MMP-2 is related to the increase in reactive astrocytes around the cyst. Middle cerebral artery occlusion for 90 min with reperfusion in SHR caused a biphasic opening of the BBB with a transient opening at 3 h and a second more severe injury at 48 h (Rosenberg et al, 1998). The early opening at 3 h correlated with an increase in MMP-2, while a later opening at 48 h correlated with increased expression of MMP-9.…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 92%